Manajemen Kepala RA di Bidang SDM Guru dalam Peningkatan Mutu Pendidikan (Studi Kasus di RA Nurul Hidayah Jembayat Kecamatan Margasari) - Eni Rakhmawati (La-Tahzan: Jurnal Pendidikan Islam, 2020)
This study examines the RA Head Management in the field of teacher HR. It is against this background that management owned by RA is not very good in the field of Teacher HR. This causes a lack of public trust in education held at RA Nurul Hidayah Jembayat Margasari. The purpose of this study was to determine the profile of coconut management in RA Nurul Hidayah Jembayat Margasari and provide recommendations for the formula for the Management of RA Heads in the field of Human Resources in Improving the quality of education in RA Nurul Hidayah Jembayat Margasari. Research methods using a qualitative approach, data analysis techniques using data reduction, with the method of taking data through observation, interviews and documentation. The data obtained are presented in a qualitative form and then conclusions are drawn as well as checking the validity of the data, extension of observation and perseverance. The results of this study are that RA Nurul Hidayah Jembayat Margasari has the goal of helping to lay the foundation towards the development of attitudes, knowledge, skills and creativity needed by students in adjusting to the environment. Its existence is used as a forum and trust by the local community to educate the children of the nation so that these children can develop in accordance with the educational goals to be achieved by RA Nurul Hidayah Jembayat Margasari. The strategy efforts undertaken are divided into 3 types, namely strategies in the field of human resources, strategies in the field of management and strategies in the field of facilities and infrastructure. Principal management maximizes human resources through training and education for teachers to produce abilities and increase knowledge in teaching students according to established standards.